The prevalence of trimester-specific dietary supplements and associated factors during pregnancy: An observational study - Liu, Ying; Guo, Nafei; Feng, Haoxue; Jiang, Hui (Frontiers in Pharmacology, 2023)
Objectives: This study aimed to assess the prevalence of trimester-specific dietary supplements (DS)s use and their possible correlates during pregnancy. Method: Pregnant women were convenience sampled and recruited from a comprehensive obstetric care center in Shanghai, China. Data relating to the use of DS during pregnancy, social support and other social-demographic and obstetric data were collected. Trimester-specific DS use and factors related DS were explored. Results: Of the 2803 women participating in this study, 94.8%, 96.2%, 93.8%, and 94.4% reported the use of at least one DS during pregnancy (all trimesters) and in the first, second, and third trimesters of pregnancy, respectively. Significant differences were noted in the use of DS containing folic acid, calcium, iron, vitamins, and docosahexaenoic acid (DHA), during the three trimesters of pregnancy. A higher proportion of DS use was negatively associated with certain categories of pregnant woman, including unemployed/housewife, low education level, obese, and low social support. A positive association was identified with gestational age. Conclusion for practice: Considering the high prevalence of DS use during pregnancy, future studies are needed to evaluate the accuracy and suitability of DS usage during pregnancy.